Financial Management Strategies to Increase the Quality of Reading Literacy - Mulyaningsih, Ely; Hartini, Yanti; Mujiarti, Atie; Mayasari, Dina; Sianturi, Risbon; Nur, Lutfi (Edulib, 2022)
An elementary school is a learning environment that serves as a springboard for kids' development into Pancasila-like individuals. Because the only source of revenue is school operational aid, students have difficulty finding other sources of income. It is impossible to optimize the financing components to improve reading literacy. This occurs as a result of the fact that educational policies influence school financial policies. The dualism of rules, notably the Ministry of Home Affairs and the Ministry of Education and Culture, must also be considered when discussing financing. As a result, determining the efficacy of reading literacy development programs is difficult. Based on this description, a Financial Management Strategy for Improving the Quality of Reading Literacy is required. This research aims to show how strategic planning is employed, how the strategy is implemented, and what the results of the financial management strategy are. This study takes a qualitative approach and uses the case study method. The research found that the school, in collaboration with the parents' association, conducts strategic planning, and the committee is planning the optimization of the school library, which is managed by teachers and associations, as well as the activation of book maintenance, which is charged to the borrower. During the implementation of this technique, the parents' association takes turns as a library manager, manages the agreement's results on maintenance fees, and teachers merely assist with reading and writing activities, as well as school literacy competitions. As a result of this technique, pupils are more familiar with reading literacy exercises, and libraries that were previously unaccredited are now accredited.